Protocol development for lipase assay on crude earthworm extract. - Mirasol, Majal Abe B (2005.)
This study was conducted in order to develop a lipase assay protocol that is sensitive to earthworm lipase. The published protocol of Kwon and Rhee (1986), which was applied by Saisuburamaniyan, et al. (2004) on soil lipase, was modified to enhance the detection of earthworm lipase. The modifications focused on the preparation of reagents, the extraction of the enzyme, and finally, on the extraction of the analyte. This developed assay procedure was then used to characterize the lipase of the native earthworm species found at Miagao (Philippines). The results showed that the developed assay was successful, in that lipase activity linearity data had been collected with linear regression of r = 0.98636. It was further shiwn that the earthworm lipase had its optimal activity at the pH range between 5.93 and 6.90, and at the temperature range within 35 degrees centigrade and 45 degrees centigrade.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Earthworm